In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism